Green Human Resource Management As A Strategy To Strengthen The Maritime Industry In Developing Green Transportation Technology - Kristiyanti, Mariana; Intan Ratna Wati (Nama Jurnal Akmi, 2026)
Purpose – This study aims to identify the maritime industry in improving sustainability-oriented performance, and how green organizational culture shapes the capabilities of low-emission technological innovation in the maritime industry. Methodology – The research used a qualitative approach with multiple case study designs on 12 shipping companies selected through purposive sampling based on commitment to sustainability programs. Data was collected through in-depth interviews with 36 informants consisting of directors, human resources managers, and technical managers, as well as through analysis of company policy documents and sustainability reports. Data analysis was carried out using thematic coding techniques and content analysis to identify the pattern of relationships between Green Human Resource Management practices and the development of green transportation technology. Findings – The results of the study show that the integration of human resource strategy with the vision of green innovation increases organizational readiness, cross-functional collaboration, and accelerates the adoption of environmentally friendly technology. Originality – This research lies in the development of an empirical evidence-based conceptual framework that links green human resource management with technological transformation in the maritime industry